ANALISIS VEGETASI HUTAN DI SEKITAR GUNUNG WANI, SUAKA MARGASATWA BUTON UTARA SULAWESI TENGGARA - Muhammad Mansur (Jurnal Teknologi Lingkungan, 2005)
Study of plant ecology in around of Wani Mountain, Buton Utara GamePreserve, South-East Sulawesi, was conducted in April 2004. Two plots each 0,5 ha (50x100m) on 300 and 400 m a.s.l were established. As the result, the forest type is low land primary forest, which inclination land is steep. There were 106 species from 78 genus and 36 families, which dominated by Pometia pinnata, Litsea albayana, Homalium foetidum, Syzygium bordenii, Kjellbergiodendron celebicum, Cleistanthus myrianthus, Orophea celebica and Polyalthia lateriflora. Number of trees noted 452 individual/ha and sapling were 3016 ha/ha. Total Basal Area of trees in two-study site is 29,71 m/ha and distribution stem diameter class were largest between on 10-20 cm.